Analysis of Mechanical Properties and Permeability of Sand Moulding by Using Eggshell in Sand Casting - Wahyu Kurnianto; Poppy Puspitasari; Wahono Wahono (Journal of Mechanical Engineering Science and Technology (JMEST), 2018)
This study aimed to analyse the usage of Eggshell as mixture material of bentonite in metal casting process which used dried sand moulding. Eggshell variations in this study were 4%, 7%, 10% eggshell, and additional 3% of bentonite on each sample. This study used pre-experimental method and included to One-Shot Case Study model. The highest strength was found on the sample 3 ES 10%. Tensile strength of dried sand moulding reach up to 0.09 kg/cm2, the compressive strength of dried sand moulding reached up to 3.11 kg/cm2, and the shear strength of dried sand moulding reached up to 1.13 kg/cm2. Based on the test result indicated that permeability of sand moulding by heat treatment at 110ºC for 60 minutes at sample of 3 ES 10% was at 178.3 ml / min.